2013
DOI: 10.1111/jeb.12218
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐generational effects of temperature on flight performance, and associated life‐history traits in an insect

Abstract: Nongenetic parental effects may affect offspring phenotype, and in species with multiple generations per year, these effects may cause life-history traits to vary over the season. We investigated the effects of parental, offspring developmental and offspring adult temperatures on a suite of life-history traits in the globally invasive agricultural pest Grapholita molesta. A low parental temperature resulted in female offspring that developed faster at low developmental temperature compared with females whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…First, we found that in C. capitata flight performance increased with increasing test temperature, largely as might be expected based on other previous examinations of insect flight (e.g. Frazier et al, 2008;Kristensen et al, 2008;Chidawanyika and Terblanche, 2011;Ferrer et al, 2013). A substantial influence of thermal history on adult flight performance was also found, with the major result being that cooler developmental temperatures resulted in improved flight ability at cooler test temperatures.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…First, we found that in C. capitata flight performance increased with increasing test temperature, largely as might be expected based on other previous examinations of insect flight (e.g. Frazier et al, 2008;Kristensen et al, 2008;Chidawanyika and Terblanche, 2011;Ferrer et al, 2013). A substantial influence of thermal history on adult flight performance was also found, with the major result being that cooler developmental temperatures resulted in improved flight ability at cooler test temperatures.…”
Section: Discussionsupporting
confidence: 64%
“…Berwaerts et al, 2002;San Martin y Gomez and Van Dyck, 2012;Ferrer et al, 2013), these effects are less straightforward than what might have been expected based on prior work from Drosophila species, for example. However, we employed a distinctly different approach to typical assessments of rearing temperature on fly morphology.…”
Section: Research Articlementioning
confidence: 60%
See 2 more Smart Citations
“…However, when cross-generational effects are important, environmental changes between generations, e.g. unpredictable changes in temperature, may result in plastic responses becoming maladaptive [4345]. We observed cross-generational costs of winter acclimatization in egg-to-adult viability at high temperatures in the field flies.…”
Section: Discussionmentioning
confidence: 81%